STUDIES ON SOIL NEMATODES OF MANIPUR -X : SPECIES OF THE FAMILY QUDSIANEMATIDAE - MOHLAL, N.; DHANACHAND, CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Four species belonging to the family Qudsianematidae latinajpuri 1965 of Nematoda are reported. One of the species Labronema sphincta is proposed as a new one. It is characterised by having a slightly curved body, 1.4-1.6mm long, an odontostyle 22. 4um long, amphidelphic reproductive system, digitate tail 30.4-32.0um long in females and presence of 8 spaced venitromedian supplements in males.